Escuela de Música - Zúñiga Chaves, Nuria (Editorial Universidad Nacional (EUNA), 2014)
The history of the School of Music of the Universidad Nacional is told from the testimonial voices of educational protagonists. Retired and active academics who have had or have important musical pedagogical contributions for the development of the School and national culture were selected.